Analysis of the pharmacotherapeutic profile of prescriptions of a masterful veterinary pharmacy in Belém (PA) (Research, Society and Development, 2022)
Masterful practice consists in the manipulation and production of pharmaceutical substances to facilitate treatment as needed by the patient. For effectiveness in veterinary treatment they need adaptations, whose market is still little explored by the pharmacist. In this sense, this study aimed to analyze the profile of veterinary prescriptions of a compounding pharmacy in Belém-PA, from April to May 2021. For this, a quantitative analysis was performed through a basic, explanatory, retrospective observational documental analysis, in which prescriptions were collected with masterful formulas of veterinary prescriptions restricted to domestic animals (dogs and cats), where the prevalence of types of pharmaceutical forms, drugs and their pharmacological classes and prescription errors were evaluated. According to the sampling calculation, the number of prescriptions analyzed were 288, of these 83.33% were destined to dogs and 16.67% to cats. It was possible to define that the profile of prescriptions was characterized as simple prescriptions (77.50%), legible (97.56%), digitized (65.0%), with no erasures or amendments (98.33% and 97.29%), 96.18% are prescribed by veterinarians, following the criteria established in the current regulations. No prescriptions were found, with drug interaction or that did not have applicability for pet. Therefore, prescriptions were observed in most of them for dogs, legible, with qualified prescriber and pharmacotherapy without special control within the protocols established by the legislation. It is notepoint that this market is vast and promising, and the pharmacist can act leading health promotion through pharmaceutical care.